Modified atmosphere packaging (MAP) of minimally processed pre-cut mixed vegetables for pinakbet - Manalang, Benedick Intal; Acevedo, Teresita P. (2002)
ABSTRACT Minimally processed pre-cut mixed vegetables for pinakbet were packed under modified atmosphere packaging (MAP) in order to prolong the shelf life. Pre-cut vegetables for pinakbet were packaged in different films specifically laminated Nylon/PE, polypropylene (PP) and low density polyethylene (LDPE) and stored at ambient condition (18-25°C) for 3 days. Discoloration, textural change and acidic odor were monitored to determine the suitable packaging film. Pre-cut vegetables packed in PP film showed the least color and textural deterioration. Minimal sour odor was also observed in the sample during the 3 days storage. After the best packaging film was selected, the product was gas packed with carbon dioxide using PP films and stored at refrigerated temperature (8-10°C) for 7 days. pH, % titrable acidity, peroxidase activity, moisture content, total plate count (TPC) and yeast & molds count were monitored during storage. the product showed minimal changes in pH, %TA and peroxidase activity. Moisture contents of individual vegetables showed an increasing trend. TPC of gas-packed samples were higher than non-gas packed samples. However, gas-packed samples showed lower yeast and mold count.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Vegetables; Vegetables -- Packaging